2017
DOI: 10.1186/s13041-017-0341-8
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal calpain is required for the consolidation and reconsolidation but not extinction of contextual fear memory

Abstract: Memory consolidation, reconsolidation, and extinction have been shown to share similar molecular signatures, including new gene expression. Calpain is a Ca2+-dependent protease that exerts its effects through the proteolytic cleavage of target proteins. Neuron-specific conditional deletions of calpain 1 and 2 impair long-term potentiation in the hippocampus and spatial learning. Moreover, recent studies have suggested distinct roles of calpain 1 and 2 in synaptic plasticity. However, the role of hippocampal ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 87 publications
1
6
0
Order By: Relevance
“…Increased local Ca 2+ amount and its influx enhance CAPN2 gene expression in tumor tissues. Previous studies have demonstrated that calpain inhibitors block Ca 2+ and signal transduction pathway. , …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased local Ca 2+ amount and its influx enhance CAPN2 gene expression in tumor tissues. Previous studies have demonstrated that calpain inhibitors block Ca 2+ and signal transduction pathway. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that calpain inhibitors block Ca 2+ and signal transduction pathway. 31,32 Confirmation of Recovered Fluorescence Signals in Tumor Tissues. Further confirmation of HSA−CAPN2 target efficacy in tumor tissues, immunohistochemistry, and tissue clarity were performed.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This Ca ++ ‐dependent protease is closely involved in the cytoskeleton remodeling that maintains the morphology of the dendritic spines (Lu et al, 2000; Simpkins et al, 2003; Wu & Lynch, 2006). Calpain modulates mnemonic processes such as consolidation, retrieval, and reconsolidation in rodents (Nagayoshi et al, 2017; Popik et al, 2018). Here, we reported that the calpain inhibitor PD150606 blocked the memory updating by deconditioning (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Given its essential role in spatial, associative and context-dependent learning (for a review see McDonald and Mott, 2017), the hippocampus seems a likely location for the encoding of context-dependent extinction learning. Indeed, a specific role for the hippocampus in the extinction of conditioned aversive experience has been proposed (Vianna et al, 2003; Bouton et al, 2006; Herry et al, 2010; Orsini et al, 2011; Cleren et al, 2013; Chang et al, 2015; Nagayoshi et al, 2017). To what extent the hippocampus contributes to extinction learning of appetitive experience is less clear, although this seems likely (Conejo et al, 2013; Méndez-Couz et al, 2014, 2015b).…”
Section: Introductionmentioning
confidence: 99%